Bacteriophage P2-71: a promising therapeutic against multidrug-resistant Proteus mirabilis in urinary tract infections - Wu, Ruihu; Dong, Zhiyou; Liu, Yunjiang; Xin, Jialiang; Duan, Yuxi; Zheng, Haohong; Yang, Yizhou; Fu, Hualin; Zhong, Zhijun; Liu, Haifeng; Zhou, Ziyao; Huang, Yixin; et al. (Frontiers in Veterinary Science, 2024)
BackgroundProteus mirabilis is a Gram-negative, rod-shaped bacterium widely found in natural environments. It is known for causing a range of severe illnesses in mammals, particularly urinary tract infections (UTIs). This study evaluates the therapeutic efficacy of phage P2-71 against Proteus mirabilis in vivo and in vitro environments.MethodsThe in vitro therapeutic potential of bacteriophage P2-71 was assessed through the ability of phage to kill Proteus mirabilis by using a plate counting assay, and biofilm inhibition and biofilm lysis assays using a microtitre plate method. Additionally, an in vivo UTI model in C57BL/6Jmice was developed via urethral inoculation of the bacterium. Phage therapy was administered through urethral injection over a period of 5 days. Therapeutic outcomes were measured by analyzing bacterial load, phage titer, inflammatory markers, and histopathological changes in the urine, urogenital tissues, and spleen.ResultsIn vitro, bacteriophage P2-71 achieved significant reductions in P. mirabilis concentrations, with log reductions of 1.537 and 0.7009 CFU/mL in laboratory and urine environments, respectively (p < 0.001). The phage also decreased biofilm formation by 34–49% and lysed 15–25% of mature biofilms at various multiplicities of infection (MOIs) (p < 0.001). In vivo, phage treatment significantly lowered bacterial concentrations in the urine on Days 1 and 3 (p < 0.0001), achieving a maximum reduction of 4.602 log₁₀ CFU/mL; however, its effectiveness diminished by Day 5 (p > 0.05). Concurrently, phage titers decreased over time. Importantly, phage treatment notably reduced bacterial load in the bladder, kidneys, and spleen (p < 0.001). Inflammatory markers such as IL-6, IL-1β, and TNF-α were significantly lower in the treatment group, especially in the bladder (p < 0.0001), indicating an effective reduction in inflammation. Histopathological analysis showed significant mitigation of tissue damage.ConclusionThe results demonstrated that bacteriophage P2-71 is a promising alternative therapy for UTIs caused by MDR Proteus mirabilis. This bacteriophage therapy offers a viable strategy for managing infections where traditional antimicrobials fail, highlighting its potential in clinical applications.